MODEL SISTEM DINAMIK KETERSEDIAAN SINGKONG BAGI INDUSTRI TAPE DI KABUPATEN JEMBER - Bambang Herry Purnomo; Ahmad Subayri; Nita Kuswardhani (JURNAL AGROTEKNOLOGI, 2015)
As we know, fermented cassava (TAPE in indonesian language) is one of popular food in Jember Regency. There are a lot of fermented cassava industry at Jember Regency. One of the major problem for fermented cassava industry is decreasing of cassava production. The aim of this research was to design a dynamic system model of cassava availability for fermented cassava industry using dynamic system methods. Model of cassava availability consist of 3 sub models; model of supply, model of consumption and model of industrial demand. Based on simulation results it was known that in 2004-2013 the availability of cassava continues to decrease.The decreasing happenned because tape industry is only able to produce 60% of its maximum capacity. Therefore, it is needed to build scenarios that meet the needs of cassava for tape industries. The result shows four scenarios orientated to the model; 1. Scenario partnership, on this scenario the need of cassava for fermented cassava industry can be met, but make the needed cassava for consumption not fullfilled; 2. partnership scenario and acreage extension plant out as big as 2% per year, this scenario can't meet the need cassava for fermented cassava industry up to next 10 years; 3.The third scenario, partnership scenario and productivity step-up as big as 20 kw/ha is not overdose give influences even have can meet the need cassava next 10 years. The fourth scenario, partnership scenario and combined scenario, combination of scenarios 2 and 3, can supply cassava for the next 10 year.Keywords: Dynamic System Model, production, availability, scenario